Comparison between robotic‐assisted and laparoscopic sphincter‐preserving operations for ultra‐low rectal cancer. Issue 5 (15th March 2022) - Kojima, Tadahiro; Hino, Hitoshi; Shiomi, Akio; Kagawa, Hiroyasu; Yamaoka, Yusuke; Manabe, Shoichi; Kato, Shunichiro; Hanaoka, Marie
Abstract: Aim: Sphincter‐preserving operations for ultra‐low rectal cancer include low anterior and intersphincteric resection. In low anterior resection, the distal rectum is divided by a transabdominal approach, which is technically demanding. In intersphincteric resection, a perineal approach is used. We aimed to evaluate whether robotic‐assisted surgery is technically superior to laparoscopic surgery for ultra‐low rectal cancer. We compared the frequency of low anterior resection in cases of sphincter‐preserving operations. Method: We investigated 183 patients who underwent sphincter‐preserving robotic‐assisted or laparoscopic surgery for ultra‐low rectal cancer (lower border within 5 cm of the anal verge) between April 2010 and March 2020. The frequency of low anterior resection was compared between laparoscopic and robotic‐assisted surgeries. The clinicopathological factors associated with an increase in performing low anterior resection were analyzed by multivariate analyses. Results: Overall, 41 (22.4%) and 142 (77.6%) patients underwent laparoscopic and robotic‐assisted surgery, respectively. Patient characteristics were similar between the groups. Low anterior resection was done significantly more frequently in robotic‐assisted surgery (67.6%) than in laparoscopic surgery (48.8%) ( P  = 0.04). Multivariate analyses showed that tumor distance from the anal verge ( P  < 0.01) and robotic‐assisted surgery ( P  = 0.02) were significantly associated with an increase in the performance of low anterior resection. The rate of postoperative complications or pathological results was similar between the groups. Conclusion: Compared with laparoscopic surgery, robotic‐assisted surgery significantly increased the frequency of low anterior resection in sphincter‐preserving operations for ultra‐low rectal cancer. Robotic‐assisted surgery has technical superiority over laparoscopic surgery for ultra‐low rectal cancer treatment. Abstract : Dividing the distal rectum via the transabdominal approach is technically demanding, and the type of sphincter‐preserving operations (SPOs) for ultra‐low rectal cancer that can be performed, including low anterior (LAR) and intersphincteric resection (ISR), depends mainly on technical factors. We compared the frequency of LAR between robotic‐assisted surgery (RS) and laparoscopic surgery (LS) in patients who underwent SPOs for ultra‐low rectal cancer to evaluate whether RS was technically superior to LS. RS significantly increased the frequency of LAR in SPOs for ultra‐low rectal cancer, supporting that RS has technical superiority over LS for the treatment of ultra‐low rectal cancer.